Exploring the implementation of an internet based rehabilitation programme for HIV adults in a public health centre - Msimanga, Lerato (My University, 2016)
Abstract South Africa has one of the largest population of adults living with HIV. About 30 to 60% of people living with HIV have been found to have HAND which can affect treatment with HAART which requires 95% compliance rate in order to be effective. Interventions that seek to alleviate the cognitive deterioration that is associated with HIV can include Internet based rehabilitation programmes. However, internet based interventions are plagued by poor adherence and attrition rates. The aim of the study was to describe the challenges and facilitating factors in the process of implementing the CogMed™ Working Memory Training Programme at a public HIV clinic for adults living with HIV. The study used a qualitative method with an ethnographic approach. Data was collected through CogMed™ administrator console, observations, interactions with gatekeepers, interactions and interviews with participants and interviews healthcare workers. The factors involved in the implementation process were categorised into the four “Stages of Use”. In the Recruitment/Consideration Stage perception of need, identifying and defining an ideal user were the main themes. Factors affecting the Initiation of Use Stage were sense of obligation, time to commit and access to suitable training environment. Utilisation of Service was influenced by ease of drop out, ease of use, perceived cost versus the perceived benefits of participating. Predisposing, enabling, and needs factors that affected adherence and participation were explored. Finally the Outcomes Stage covered the experiences and perceptions of using the rehabilitation tool. Limitations of the study were also discussed. Keywords: CogMed, Working Memory, HIV, HAND, Internet based interventions, Stages of Use
Keywords: CogMed; Working memory; HIV; HAND; Internet based interventions; Stages of use